CARDIAC MAGNETIC RESONANCE IMAGING IN THE EARLY DIAGNOSIS OF ISCHEMIC HEART DISEASE: A QUANTITATIVE CLINICAL AND STATISTICAL ANALYSIS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Ischemic heart disease (IHD) remains a major contributor to cardiovascular morbidity and mortality worldwide, largely due to delayed recognition of myocardial ischemia at its early and potentially reversible stages. Conventional diagnostic methods often fail to detect subtle ischemic changes, particularly in patients with atypical clinical presentations or preserved ventricular function. The present study evaluates the diagnostic performance of cardiac magnetic resonance imaging (CMR) in the early detection of myocardial ischemia using quantitative functional, perfusion, and tissue characterization parameters. A prospective study involving 192 patients with suspected IHD was conducted. All participants underwent comprehensive CMR evaluation, including cine imaging, stress-rest perfusion, and late gadolinium enhancement (LGE). The diagnostic accuracy of CMR was compared with electrocardiography, transthoracic echocardiography, and invasive coronary angiography. Statistical analysis revealed that CMR demonstrated significantly higher sensitivity (91.3%) and specificity (88.6%) in detecting early ischemic changes compared to conventional modalities. The results confirm the pivotal role of CMR as a non-invasive, high-precision diagnostic tool for early ischemic heart disease.